2017
DOI: 10.1186/s12889-017-4417-2
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of HIV testing in Burkina Faso: an assessment of individual and community-level determinants

Abstract: BackgroundPrevious studies have highlighted a range of individual determinants associated with HIV testing but few have assessed the role of contextual factors. The objective of this paper is to examine the influence of both individual and community-level determinants of HIV testing uptake in Burkina Faso.MethodsUsing nationally representative cross-sectional data from the 2010 Demographic and Health Survey, the determinants of lifetime HIV testing were examined for sexually active women (n = 14,656) and men (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
60
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 43 publications
26
60
4
Order By: Relevance
“…Compared to males who were not working and didn't work in last 12 months before the interview, the odds of getting tested for HIV/AIDS for professional workers surpasses by about two-fold; whereas the odds for the males engaged in trade/sales, elementary and other types of work are on the upper hand by about 73.2%, 46.3%, and 83.6% respectively. The current nding is consistent with the results elicited by studies conducted in Burkina Faso and Soweto, South Africa (21,22). This is reasonably due to exposure to different workplaces than agriculture is expected to give a different level of access to information about VCT services and bene ts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compared to males who were not working and didn't work in last 12 months before the interview, the odds of getting tested for HIV/AIDS for professional workers surpasses by about two-fold; whereas the odds for the males engaged in trade/sales, elementary and other types of work are on the upper hand by about 73.2%, 46.3%, and 83.6% respectively. The current nding is consistent with the results elicited by studies conducted in Burkina Faso and Soweto, South Africa (21,22). This is reasonably due to exposure to different workplaces than agriculture is expected to give a different level of access to information about VCT services and bene ts.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas, the odds of getting tested for HIV/AIDS for males who watch TV at least once a week surpasses that of males who do not watch TV at all by about 29%. This result is similar to the ndings from Zimbabwe and Burkina Faso where exposure to media was positively associated with HIV VCT uptake (21,29). Evidence from the analysis of the 2016 Uganda DHS showed that listening to radio once a week and watching television more than once a week increases the odds of being tested for HIV by 4.57% and 8.57% respectively (33).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We allow for changes in this ratio from 2005 and 2010 to account for potential scaling-up of prevention of mother-to-child transmission programs in sub-Saharan Africa countries [18,19] , which could have influenced sex differences in HIV testing uptake. The term Aki is the age-and sex-specific HIV testing rate ratio for ages 15-24 (i=1), 25-34 (i=2), 34-49 (i=3), and 50+ (i=4) age groups, which are assumed to be time-invariant [8,14,20,21] .…”
Section: Model Specification For Hiv Testingmentioning
confidence: 99%
“…Determinants of HIV testing among men has been studied in several reports , including analyses of Demographic and Health Surveys (DHS) . Existing evidence shows that men who were younger , had less education , did not have an occupation , had stigmatising views of HIV and who lacked HIV knowledge were more likely to report never testing for HIV. In this study, we sought to characterize men who had never tested for HIV in sub‐Saharan Africa, understand the factors associated with not testing, and measure men's uptake and positivity rates when offered HIV testing in a survey setting.…”
Section: Introductionmentioning
confidence: 99%